Health literacy strengths and needs among migrant communities from Portuguese-speaking African countries in Portugal: a cross-sectional study - Maia, Ana Catarina; Marques, Maria João; Goes, Ana Rita; Gama, Ana; Osborne, Richard; Dias, Sónia (Frontiers in Public Health, 2024)
Introduction: Health literacy among migrants is a matter of public health and social justice. Migrants from diverse backgrounds encounter linguistic barriers, cultural disparities, restricted access to health services, and heterogeneous migration statuses. Addressing these challenges requires careful consideration of their unique experiences and needs to promote equitable health outcomes. This can hinder their ability to navigate the healthcare system, understand health information, and engage in health-promoting behaviours. However, there is still a significant gap in our understanding of health literacy within migrant communities. This study has a dual aim: to identify health literacy strengths and needs among migrants from Portuguese-speaking African Countries (PALOP) in the Lisbon Metropolitan Area and to examine associations between demographic, socioeconomic, migration and health condition characteristics and the health literacy domains. Methods: A cross-sectional survey was conducted. Data were collected from 506 PALOP migrants using the Health Literacy Questionnaire (HLQ). We also collected demographic, socioeconomic, migration, and health condition data. We employed multiple linear regression to understand the relationship between the HLQ nine domains and these characteristics. Results: The HLQ scores revealed distinct patterns of health literacy between the groups. Health literacy needs were particularly evident in the domains related to feeling understood and supported by healthcare providers and navigating the healthcare system. Conversely, higher scores and potential strengths were observed in actively managing one's health and understanding enough health information to make informed decisions. However, the average scores suggest that many people recognized difficulties. The results also indicated that a higher educational level was associated with increased health literacy. In contrast, low self-perceived health status, living alone, shorter duration of residence in Portugal, and being either undocumented or in the process of obtaining legal status were associated with lower health literacy. Conclusion: Our study highlights the importance of migration-related variables and self-reported health status in understanding health literacy among migrant communities. Factors such as length of stay and low self-perceived health status are associated with potentially disadvantageous levels of health literacy, which could exacerbate health inequalities. Assessing these variables is critical to identify gaps in health literacy and develop tailored interventions to reduce health inequalities.